Sleeping in Beowulf - Dubs, Kathleen (American & British Studies Annual, 2010)
“Now I lay me down to sleep, I pray the Lord my soul to keep; if I should die before I wake, I pray the Lord my soul to take.” As this well-known little prayer suggests, during actual sleep—while the conscious faculties are inoperative—the soul is at risk. Indeed, during sleep the body is also in danger, as the unconscious man is not alert to threat. Apparently sleeping can be a dangerous (in)activity. In the Old English poem Beowulf, actual sleeping occurs at critical points in the narrative, but always at night, or at least in darkness. Moreover, the traditional literary uses of sleep as a simulacrum of death also occur. But correlations among these concepts are not consistent. Beowulf usually fights at night, without sleep; he is, at least once, saved from death by his ability to stay awake. But he also fights during the day, though with different results. The monsters attack at night, in the darkness, so apparently they, too, do not sleep at night. But the dragon sleeps night and day until awakened, in the night, when he attacks regardless of the hour, though he is a night flyer. Thus much of the activity in Beowulf occurs at night, or in the dark, but the results are revealed only in the light of dawn. This paper investigates the different occurrences of sleep, in their various contexts, as well as in their relationships to light and darkness, and analyses their contributions to larger meanings within the poem. It concludes that sleep is a representation of inattentiveness, the result of which is usually fatal, physically as well as spiritually.